Effects of stumping on fine root architecture, growth, and physiology of Hippophae rhamnoides - Wang, Haoyue; Qi, Wei; Guo, Yuefeng; Xu, Yajie (PeerJ, 2023)
Background Fine roots are vital to a plant’s ability to absorb water and nutrients. Stumping is a practice that may encourage fine root growth and the rapid recovery of decaying Hippophae rhamnoides plants. However, the effect of stumping on the fine roots and physiological indices is still unknown. The differential indices between stumped forests and non-stumped forests must also be defined. Methods We recorded the changes in the fine roots of structure H. rhamnoides one year after stumping. Using single factor analysis of variance and general linear models we comprehensively analyzed the number of root tips and the plant’s growth and physiological indices in response to stumping. Partial least squares discriminant analysis (PLS-DA) was used to compare fine root growth and physiological indices with and without stumping in order to identify the differential indices. Results The proportion of root tips in the vertical layers at 30–40 cm and 40–50 cm and in the horizontal layers at 60–80 cm and 80–100 cm, increased after stumping by 1.85%, 2.60%, 1.96% and 4.32%, respectively. In the 0–50 cm soil layer, the fine root dry weight rose by 27.6% compared with the control, which was not significant. However, other indices were significantly different from the control. The proportions in the growth indices in the 30–40 cm and 40–50 cm layers increased after stumping. Stumping had a significant, negative effect on proline and malondialdehyde content, which dropped by 40.95% and 55.32%, respectively, indicating that the harms caused by these two chemicals was alleviated. Stumping had a significant positive effect on root activity and soluble sugar contents, which increased by 68.58% and 36.87%, respectively, and improved the growing ability of fine roots. PLS-DA revealed that malondialdehyde, soluble sugars, root density, and the number of root tips ranked from having the least to greatest effect on the classification of stumping and no-stumping. Conclusions The process of stumping may promote fine roots growth in H. rhamnoides, and is favorable for their longitudinal development. The fine root growing indices of H. rhamnoides responded positively to this process. Stumping promotes root activity and the creation of soluble sugar to maintain the growth and development of fine roots. It also inhibits the negative effects of proline and malondialdehyde on fine roots. Our study showed that the differential physiological indices were more important for classification than the differential growing indices.
Keywords: Stumping; Fine root growth characteristics; Fine root physiological characteristics; Hippophae rhamnoides; PLS-DA